2000
DOI: 10.1016/s0893-133x(00)00110-x
|View full text |Cite
|
Sign up to set email alerts
|

Buprenorphine-Induced Changes in Mu-Opioid Receptor Availability in Male Heroin-Dependent Volunteers A Preliminary Study

Abstract: Medications for the treatment of substance abuse may be developed for a variety of purposes (e.g., ameliorate toxicity, treat overdoses) but a primary goal is to attenuate the subjective, behavioral, or physiological effects of the drug of abuse. Buprenorphine is a high affinity, mu opioid partial agonist, with kappa antagonist action (Cowan et al. 1977;Heel et al. 1979;Lewis et al. 1983). This compound is being evaluated as an alternative to methadone maintenance and detoxification in the treatment of opioid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(91 citation statements)
references
References 25 publications
3
88
0
Order By: Relevance
“…Common phMRI activation was observed in a number of brain regions for the higher doses of buprenorphine (i.e., 0.1 mg/kg and 0.2 mg/70 kg for rat and human, respectively). These regions included the somatosensory cortex, cingulate, insula, thalamus, striatum, hippocampal formation, periaqueductal gray, and cerebellum, which are all implicated in pathophysiological conditions that include pain (Elman et al, 2011;Borsook, 2012;Tracey and Dickenson, 2012) and have high densities of opioid receptors (Zubieta et al, 2000;Peng et al, 2012). Thus, in large part, the phMRI signature for buprenorphine was observed to translate between conscious, naive rodents and healthy human subjects in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Common phMRI activation was observed in a number of brain regions for the higher doses of buprenorphine (i.e., 0.1 mg/kg and 0.2 mg/70 kg for rat and human, respectively). These regions included the somatosensory cortex, cingulate, insula, thalamus, striatum, hippocampal formation, periaqueductal gray, and cerebellum, which are all implicated in pathophysiological conditions that include pain (Elman et al, 2011;Borsook, 2012;Tracey and Dickenson, 2012) and have high densities of opioid receptors (Zubieta et al, 2000;Peng et al, 2012). Thus, in large part, the phMRI signature for buprenorphine was observed to translate between conscious, naive rodents and healthy human subjects in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging techniques are being increasingly used as translational neuroscience tools, particularly in drug discovery and development efforts. Methods such as PET and SPECT are useful when characterizing a central nervous system disease state (eg, b-amyloid build up in patients with Alzheimer's disease (Nordberg, 2004) or dopaminergic terminal function in patients with Parkinson's disease (Sawle et al, 1993;Marek et al, 1996) and also as a means to determine whether a pharmacological compound has engaged its target [eg, buprenorphine at m-opioid receptor (Zubieta et al, 2000) or aprepitant at NK-1 receptors (Keller et al, 2006)]. Proving the presence of specific target in a preclinical model or disease state and robust target engagement are extremely important to determine.…”
Section: Discussionmentioning
confidence: 99%
“…Since the rewarding effects of buprenorphine are likely to be mediated by d-and k-opioid receptors in addition to m-opioid receptors, buprenorphine might conceivably provide a prototype for clinical effectiveness through decreased m-opioid receptor availability (Greenwald et al, 2003;Zubieta et al, 2000). Such m-opioid receptor-selective partial agonists might even provide good adjuncts during detoxification.…”
Section: Effects Of Buprenorphine In Mor-ko Micementioning
confidence: 99%
“…Zubieta et al (2000) reported an increase in l receptor availability in the VTA, inferofrontal cortex, and anterior cingulate in heroin-dependent subjects compared with control subjects using [ 11 C] carfentanil PET. Kling et al (2000) performed a study using [ 18 F] cyclofoxy, an opioid antagonist that labels l and j opioid receptors, in methadone maintained heroin-dependent subjects.…”
Section: Heroin-induced Da Increases In the Brain And Reinforcementmentioning
confidence: 99%